1990
DOI: 10.1073/pnas.87.19.7565
|View full text |Cite
|
Sign up to set email alerts
|

Sterol phylogenesis and algal evolution.

Abstract: The stereochemistry of several sterol precursors and end products synthesized by two fungal-like microorganisms Prototheca wickerhamii (I) and Dictyostelium discoideum (H) have been determined by chromatographic (TLC, GLC, and HPLC) and spectral (UV, MS,-and 'H NMR) methods. From I and H the following sterols were isolated from the cells : cycloartenol, cyclolaudenol, 24(28)-methylenecycloartanol, ergosterol, protothecasterol, 4a-methylergostanol, 4a-methylclionastanol, clionastanol, 2413-ethylcholesta-8,22-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 41 publications
(39 reference statements)
5
63
0
Order By: Relevance
“…KD7PY cells accumulated trace amounts of cyclolaudenol and 24(28)-methylenecycloartanol along with minor amounts of 4 ␣ ,14 ␣ -dimethylporifersta-8,25(27)-dienol ( Table 2 ). The mass spectra of the structural isomers cyclolaudenol and 24(28)-methylenecycloartanol are almost identical to each other and, depending on the nature of the GC column, they coelute as we reported previously ( 13 ) ( Fig. 5 ).…”
Section: General Consideration For Ergosterol Biosynthesis In C Reinsupporting
confidence: 61%
See 1 more Smart Citation
“…KD7PY cells accumulated trace amounts of cyclolaudenol and 24(28)-methylenecycloartanol along with minor amounts of 4 ␣ ,14 ␣ -dimethylporifersta-8,25(27)-dienol ( Table 2 ). The mass spectra of the structural isomers cyclolaudenol and 24(28)-methylenecycloartanol are almost identical to each other and, depending on the nature of the GC column, they coelute as we reported previously ( 13 ) ( Fig. 5 ).…”
Section: General Consideration For Ergosterol Biosynthesis In C Reinsupporting
confidence: 61%
“…Based on spectra of reference materials ( 31,37,38 ), the sterols from the different cell types possessed one or more functional groups of a ⌬ 22 E double bond, Relevant ions for ergosterol appeared at m /-396, 381, 378, and 363 amu and for 7-dehydroporiferasterol at m / z 410, 395, 392, and 377 amu ( Fig. 3 ) (27) -olefi n intermediate, analogous to 24 ␤ -methyl sterols in other green algae (Chlorella and Trebouxia; 22,40 ) and in the nonphotosynthetic, Chlorellalike alga Prototheca ( 13,41 ). Our results rule out the ⌬ 24 (28) olefi n pathway used in fungal ergosterol biosynthesis ( 39,42 ) because, in the fungal pathway, the methyl groups in 24-methyl and 24-ethyl sterols incorporate two and four deuterium atoms, respectively ( Fig.…”
Section: Induced Accumulation Of Sterol Intermediatesmentioning
confidence: 99%
“…1). Through comparison of published NMR and EI-MS data, the structures of the known compounds were identified as cycloartenol (1), 35,36) p-hydroxybenzoic acid (2), 37) vanilloloside (3), 38) and 5Ј-O-methyladenosine (4). 39) This is the first report of isolation of these four, known compounds 1-4 from this plant.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that CYP524 from a cellular slime mold (D. discoideum), containing the sequence conservation in the substrate recognition site (Figure 2), was located on the same branch of CYP710 proteins in the phylogenetic tree (Figure 9). D. discoideum produces 4a-methylergostanol, 24b-ethycholesta-8,22-enol, and dictyosterol as D 22 -sterols (Nes et al, 1990), suggesting the possibility that these different subfamily P450s may be involved in the same catalytic function. Sterol analysis indicated that the slime mold evolved from algal rather than from fungal ancestors (Nes et al, 1990), which is consistent with the close location of CYP524 and CYP710B in the phylogenetic tree (Figure 8).…”
Section: Cyp710 Family P450 Genesmentioning
confidence: 99%